The Russian-French Agreement on Mutual Qualifications Cecognition - an Important Stage of International Educational Cooperation - Gennady Fedorovich Tkach; Sergey Aleksandrovich Kovalenko (Vestnik RUDN. International Relations, 2016)
The article considers the historical background, organizational and legal circumstances of the development and signing of the Russian-French agreement on mutual recognition of education and (or) qualifications and degrees. The authors reveal fundamental importance of the uniform approach by comparison the basic levels of education between the two countries and the relevant qualifications. Analysis of the main substantive provisions of the joint document is provided. It is the first such full-scale agreement signed by the Russian Federation with one of the developed countries. A brief overview of the evolution of “qualifications recognition”, its concept, essence, targets and terminology are given in the initial part of the paper. The article analyzes the definitions of terms used both in the Convention on the Recognition of Qualifications concerning Higher Education in the European region and in the modern practice of the recognition of the Russian Federation. Distinction of the purpose and possibilities of conventions application and bilateral agreements on the recognition of qualifications are shown. The authors describe the sequence and content of the basic stages of development of the draft Agreement. The article displays mismatch of the two countries on the possibility of professional recognition along with academic recognition. In conclusion, the authors express confidence that the signing of the Russian-French agreement on the recognition of qualifications will promote academic exchanges and deepen cooperation between Russia and France, and will have a stimulating effect on all aspects of international educational co-operation between Russia and other countries.